Answer:
<em>p = ± q / 5r + 8; Option D</em>
Step-by-step explanation:
We are given the following equation; q^2 / p^2 - 16p + 64 = 25r^2;
q^2 / p^2 - 16p + 64 = 25r^2 ⇒ Let us factor p^2 - 16p + 64, as such,
p^2 - 16p + 64,
( p )^2 - 2 * ( p ) * ( 8 ) + ( 8 )^2,
( p - 8 )^2 ⇒ Now let us substitute this into the equation q^2 / p^2 - 16p + 64 = 25r^2 in replacement of p^2 - 16p + 64,
q^2 / ( p - 8 )^2 = 25r^2 ⇒ multiply either side by ( p - 8 )^2,
q^2 = 25r^2 * ( ( p - 8 )^2 ) ⇒ divide either side by 25r^2,
q^2 / 25r^2 = ( p - 8 )^2 ⇒ Now apply square root on either side,
| p - 8 | = √( q^2 / 25r^2 ) ⇒ Simplify,
| p - 8 | = q / 5r,
| p | = q / 5r + 8,
<em>Answer; p = ± q / 5r + 8; Option D</em>
An isosceles triangle has 2 sides the same length and 1 side of a different length
so if the 22 is the identical length then you would have another side of 22
and the 3rd side would be 71 - 22 -22 = 27 cm
so you could have 22 and 27
if the 22 is the odd length side then you would have 71 - 22 = 49 / 2 = 24.5
so you could have 24.5 and 24.5
Answer:
HI
Step-by-step explanation:
Answer:
y = 4x + 16
Step-by-step explanation:
y - 1 = 4(x + 3)
Has a slope of 4
y = 4x + c
32 = 4(4) + c
32 - 16 = c
c = 16
y = 4x + 16